Pendidikan Karakter Guru PAI Dan Orang Tua Dalam Membangun Ketahanan Moral Peserta Didik Pada Era Milenium Di Madrasah Ibtidaiyah Assu’ada Depok - Cecep Supriyadi (4, 2026)
The millennium era has brought new dynamics to the world of education, marked by the rapid development of digital technology, the rapid flow of information, and rapid socio-cultural changes. These conditions not only open opportunities for improving the quality of learning but also pose serious challenges to the development of character and moral resilience in students. At the Madrasah Ibtidaiyah (Islamic elementary school) level, these challenges are even more complex because students are in an early developmental phase and are highly vulnerable to environmental influences. This study aims to analyze in depth the role of character education carried out by Islamic Religious Education (PAI) teachers and parents in building moral resilience in students at Madrasah Ibtidaiyah Assu'ada Depok. Using a qualitative approach with descriptive methods, data were collected through observation, in-depth interviews, and documentation with informants including PAI teachers, the madrasah principal, parents, and students. The results reveal that PAI teachers play a central role as educators, mentors, and role models in the internalization of moral values, noble character, and the instilling of discipline. Character values ​​are integrated through learning, religious activities, and school culture. Parents also make a significant contribution through parenting styles, role models at home, monitoring technology use, and fostering religious practices. The synergy between the two forms a crucial force in strengthening students' moral resilience against the negative influences of the millennium, such as moral degradation, bullying, and gadget addiction. Abstrak Era milenium menghadirkan dinamika baru dalam dunia pendidikan, ditandai oleh pesatnya perkembangan teknologi digital, derasnya arus informasi, serta perubahan sosial-budaya yang begitu cepat. Kondisi tersebut tidak hanya membuka peluang bagi peningkatan kualitas pembelajaran, tetapi juga menimbulkan tantangan serius terhadap pembentukan karakter dan ketahanan moral peserta didik. Di tingkat Madrasah Ibtidaiyah, tantangan ini menjadi lebih kompleks karena peserta didik berada pada fase perkembangan awal yang sangat rentan terhadap pengaruh lingkungan. Penelitian ini bertujuan untuk menganalisis secara mendalam peran pendidikan karakter yang dilakukan oleh Guru Pendidikan Agama Islam (PAI) dan orang tua dalam membangun ketahanan moral peserta didik di Madrasah Ibtidaiyah Assu’ada Depok. Menggunakan pendekatan kualitatif dengan metode deskriptif, data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi, dengan informan yang meliputi guru PAI, kepala madrasah, orang tua, dan siswa. Hasil penelitian mengungkapkan bahwa guru PAI berperan sentral sebagai pendidik, pembimbing, dan teladan dalam internalisasi nilai moral, akhlak mulia, serta pembiasaan sikap disiplin. Nilai-nilai karakter diintegrasikan melalui pembelajaran, kegiatan keagamaan, dan budaya sekolah. Orang tua juga memiliki kontribusi signifikan melalui pola asuh, keteladanan di rumah, pengawasan penggunaan teknologi, serta pembiasaan ibadah. Sinergi keduanya membentuk kekuatan penting dalam meningkatkan ketahanan moral peserta didik dari berbagai pengaruh negatif era milenium seperti degradasi moral, perilaku perundungan, dan kecanduan gawai.